"Vernacularising Modernity?" Rural–Urban Migration and Cultural Transformation in the Northern Mandara Mountains. Issue 1 (April 2018) - Chétima, Melchisedek
This article explores the different ways in which new houses built by migrants from the Mandara Mountains to bigger cities in Cameroon function as an important site for studying their relations within the cities and within their communities of origin. I argue that these new houses constitute both a powerful resource for addressing migrants' stories about their migratory experiences and a constituent element of these experiences. In many circumstances, the migrants interviewed were unable to speak separately of their migratory experiences and their homes. Thus, the impact of their mobility to cities goes far beyond the mere ownership of the houses; they also manage to change their perceptions of themselves, to restructure their models of social interaction with other migrants, and to change the balance of their relations with the village. The article ends by proposing to connect the two sides of the village/city duality to find out how the local is a product of the global and how the local has reappropriated the global, giving it a meaning.